Decentralization: Historical Construct and Contemporary Discourse in Northeast India - Jayanta Krishna Sarmah and Daisy Nath (KILA Journal of Local Governance, 2013)
Governance of India underwent progressive changes since tDecentralization has been emerging as a dominant power sharing trend in the contemporary discourses of administration. The process of decentralization have witnessed a paradigm shift in administrative system from state control towards approaches in which people play an active role in the administration. This reform aim to increase the people’s participation in the decision making process. Power sharing in organization can be initiated by various acts such as by sharing leadership, sharing resources and encouraging participation in decision making, goal setting, and delegation of authority in the decentralization process. In this paper, attempt has been made to examine how decentralization in power sharing organizations can improve the performance and accountability of local government institutions in Northeast India, especially, Assam.